Audit of the management of patients admitted with community acquired pneumonia - Foley, S C; Kelly, E M; O'Neill, S J (Irish medical journal, 2006)
Community acquired pneumonia (CAP) is a major cause of morbidity and mortality worldwide. There is evidence that guidelines do guide and standardise management, but with less measurable effect on outcome. We prospectively audited the management of CAP in patients admitted to a Dublin hospital during the winter of 2003/04. The main objective was to evaluate the quality of care for CAP using the BTS guidelines as a standard of management. 164 patients were admitted with CAP during the defined period. Guidelines for assessment of disease severity at presentation were followed in only 56 (34.1%) cases. Appropriate antibiotic therapy was instituted within 8 hours of presentation in 123 (75.0%) cases. The rate of use of a severity assessment score to stratify patients with CAP based on recognized guidelines is low in our hospital. Despite this, the overall mortality rate of 8.5% is comparable with previous results.